Data Measurements of Harmonic and Subra-Harmonics Emission by AC Drive for Dry Milling Systems - Boonseng, C.; Boonseng, R.; Kularbphettong, K. (My University, 2019)
The ac drives which operate at a poor power factor decreases motor speed and injected large harmonic current and subra-harmonics into the supply network. The effects of harmonic and subra-harmonic that are injected into the network include overheating of transformers and motor and other instrumentation that were not designed with an insensitivity to harmonic in the supply. Thus, some form of harmonic and subra-harmonic mitigation is required. The PQube3 compact instrument is simply the best power monitor and real-time sensor and it records harmonic and supra-harmonics of AC drive for dry-milling system. To reduce the harmonic current and subra-harmonic injected in the network. The Hybrid Power Filter System(HPFs) are chosen because they can solve this problem with the least cost and the same effect as active filter. The results show that the association of HPFs is a very good solution for harmonic and subra-harmonic problems.
Keywords: electromagnetic compatibility; emission levels; harmonic; power quality; supra-harmonics